2015
DOI: 10.1155/2015/875738
|View full text |Cite
|
Sign up to set email alerts
|

Pimachrysa(Neuroptera: Chrysopidae: Nothochrysinae): Larval Description and Support for Generic Relationships

Abstract: We describe the previously unknown larval characteristics of Pimachrysa (second and third instars), and we provide new comparative data on the Nothochrysa californica Banks larvae that were described earlier. The Pimachrysa larvae (identified as Pimachrysa fusca Adams) express the numerous features that characterize the chrysopid subfamily Nothochrysinae. They resemble Hypochrysa larvae in many respects, but several differences support retaining the two genera as separate. It now appears that the reputedly mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…excluding Nothochrysa from either Nothochrysinae or from Nothochrysinae + Chrysopinae) have low support for monophyly. Although, in general, larval morphology supports the monophyly of Nothochrysinae (Tauber, ), recent studies (Duelli et al ., ; Tauber & Faulkner, ) have indicated that smaller‐bodied nothochrysines [i.e. Hypochrysa (including Kimochrysa ), Pimachrysa, and Dictyochrysa ] are more similar to each other than to Nothochrysa , which is the same pattern of relationships within Nothochrysinae supported by our results.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…excluding Nothochrysa from either Nothochrysinae or from Nothochrysinae + Chrysopinae) have low support for monophyly. Although, in general, larval morphology supports the monophyly of Nothochrysinae (Tauber, ), recent studies (Duelli et al ., ; Tauber & Faulkner, ) have indicated that smaller‐bodied nothochrysines [i.e. Hypochrysa (including Kimochrysa ), Pimachrysa, and Dictyochrysa ] are more similar to each other than to Nothochrysa , which is the same pattern of relationships within Nothochrysinae supported by our results.…”
Section: Resultssupporting
confidence: 86%
“…All species are apparently found only within closed forested habitats and no fossil representatives of this subfamily are known (Winterton & Brooks, ). Nothochrysinae is another small subfamily, with just over 20 extant species in nine genera of temperate occurrence (Adams, ; Adams & Penny, ; Duelli et al ., ; Tauber & Faulkner, ). Although represented by relatively few living species, there are numerous fossil representatives of the subfamily known from Late Cretaceous and Cenozoic deposits (Adams, ; Nel et al ., ; Archibald et al ., ); it remains to be determined, though, whether inclusion of these fossil species is justified cladistically as the fossils could represent a grade, with their inclusion based solely on plesiomorphies and thus possibly rendering Nothochrysinae paraphyletic.…”
Section: Introductionmentioning
confidence: 99%
“…Lateral tubercles are better developed than laterodorsal ones, and the latter tend to be better developed than the submedial tubercles, when present. With the exception of some naked forms (e.g., Brinckochrysa , Hypochrysa , Pimachrysa ) where tubercles are absent or vestigial 26 , 27 , extant chrysopid larvae show distinct pairs of setose tubercles on the dorsum of the three thoracic segments and of a variable number of abdominal segments. In any case, setose tubercles as dramatically elongate (=tubular) as in the Cretaceous chrysopoids are absent from modern chrysopid larvae, as their degree of development only ranges from weakly-developed (“small”), to hemispherical, papilliform, spherical, cylindrical, and digitiform.…”
Section: Discussionmentioning
confidence: 99%
“…They are divided into four tribes: Belonopterygini, Leucochrysini, Ankylopterygini and Chrysopini, of which Chrysopini are the most species-rich, followed by Belonpterygini (15 genera), Leucochrysini (7 genera), and Ankylopterygini (6 genera) [ 14 , 15 ]. Nothochrysinae contain nine extant genera with some plesiomorphic characteristics, such as the presence of a forewing jugal lobe [ 3 , 16 , 17 , 18 , 19 ]. Although there are few living species in this subfamily, their fossil records from Late Cretaceous and Cenozoic periods are abundant compared to other subfamilies [ 16 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%